Effect of Lactobacterin-TK2 and Multispecies probiotics on calf health during suckling - Özkaya, S; Işık, AR; Boranbayeva, T; Karahan, AG; Tulemissova, Z; Myktybayeva, R; Sansyzbai, A; Şanlı, ER (Journal of the Hellenic Veterinary Medical Society, 2025)
We hypothesized that supplementing probiotics to milk would improve calves’ intestinal microbiota, support the immune system and antioxidant defense mechanism, increase their live weight, and raise healthy calves. The present study aimed to investigate the effects of two probiotic mixtures (Lactobacterin-TK2 and Hypro) containing beneficial microorganisms from different sources on the immune system and growth of calves by reducing oxidative stress during the milk-suckling period. Eighteen newborn calves (n=6 in each group) were randomly selected and divided into three groups. Groups were formed as the control group (G1; without probiotics), Lactobacterin-TK2 (G2), and Hypro probiotic (G3). The administration of Lactobacterin-TK2 and Hypro probiotics caused an increase in live weight (LW, P=0.04) and daily live weight (DLW, P=0.04) and reduced the number of days with diarrhea compared to the control group. Hypro reduced the total coliform counts (P<0.05) and increased yeast counts (P<0.05) in fecal samples on 14-day-age. No adverse effects of probiotics were determined on blood biochemistry. No significant changes were determined in the oxidative and antioxidative stress parameters, except for Paraoxonase 1 (PON 1) (P<0.05). IgA, IgE, and IgG levels in the probiotic groups showed similarities with those of the control group. The findings showed that Lactobacterin-TK2 and Hypro probiotics can be used to supplement the milk of calves to provide better growth during suckling period and to raise healthy calves by reducing the effect of oxidative stress.